Modeling and Forecasting System of the Hydrological Fields in the Georgian Waters of the Black Sea and its Further Development - Demetrashvili, Demuri I. (Journals of Georgian Geophysical Society, 2025)
This paper discusses current state and further development of the high-resolution marine regional modeling and forecasting system for the Georgian sector of the Black Sea and adjacent waters, which has been developed within the EU international scientific and technical projects ARENA (2003-2006), ECOOP (2007-2010). Its further expansion with the inclusion of impurity transport models in the system was carried out within the framework of Shota Rustaveli National Science Foundation grant (2013-2015). This system, based on a regional numerical model of the Black Sea dynamics and 2-D and 3-D transport models of the impurity, provides modeling of the main hydrological fields and the spread of oil and other impurities with a spatial resolution of 1 km. In the case of providing real input data, the system makes it possible to forecast the state of the sea for several days in advance. Further development of the existing regional modeling system is related to the development of a very high-resolution modeling subsystem for the Batumi-Poti-Anaklia nearshore water area and the inclusion of a wind wave forecast model in the subsystem. The purpose of the very high-resolution modeling subsystem is to specify and make more detailed marine forecast for the Batumi-Poti-Anaklia coastal waters (with a spatial resolution of 200 m), which are subject to the greatest anthropogenic load.